Meal or mate: Exploring the evidence of sexual cannibalism among amphibians - John Gould; Chad T. Beranek (Ecology and Evolution, 2024)
Abstract Active forms of cannibalism that involve predation of live conspecifics occur widely among amphibians, most notably by tadpoles that feed on each other and adults that feed on juveniles. In contrast, cannibalism among amphibian adults (adult–adult cannibalism) is less often reported and there have been no investigations on the occurrence of sexual cannibalism in this group to date. In this study, we present an observation of potential sexual cannibalism involving an adult female green and golden bell frog, Litoria aurea, preying on a conspecific adult male during the species' breeding season. By comparing our observation to the available literature, we show that adult–adult cannibalism among amphibians is rare but tends to be committed by females against their male counterparts. We thus suggest that the occurrence of sexual cannibalism should be extended to include this group, where sexual size dimorphism occurs widely among adults that congregate spatially during breeding periods, both predictors of intra‐specific predation. We hypothesise that amphibian females may be able to exploit male advertisement calls to differentiate suitable partners from potential prey and that male individuals are vulnerable to sexual cannibalism as they must risk attracting and physically exposing themselves to females in order to reproduce. Our findings reveal the complex dynamics that exist within adult amphibian populations, suggesting that females may have a choice when deciding how to interact with and utilise their male counterparts. As our findings are preliminary, based on a small sample size of records, including several from captive individuals, we encourage authors to publish their observations of cannibalism in the field, including unsuccessful attempts, to confirm the presence of sexual cannibalism in this group.